ANALISIS PENGEMBALIAN ASET TERPIDANA TINDAK PIDANA NARKOTIKA PADA PUTUSAN MAHKAMAH AGUNG NOMOR 250K/PID.SUS/2018 MENURUT UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Dennis Nathanael Lempoy; Firman Wijaya (Fakultas Hukum Universitas Tarumanagara, 2020)
Drug dealer Murtala Ilyas commits a crime of money laundering from the results of narcotics transactions. However, in the Supreme Court Decree No. 250K / Pid.Sus / 2018, the Supreme Court judge sentenced the Defendant to an 8-year prison sentence and a fine of Rp. 5,000,000,000 and the judge returns the Asset in the Value of Rp. 142,131,500,000 to the Defendant. The problem faced in writing this thesis is whether the return of assets convicted of narcotics crime in the Decision of the Supreme Court Number 250K / Pid.Sus / 2018 in accordance with Law Number 35 of 2009 concerning Narcotics. The research method used in writing this thesis is normative legal research. The results showed that the return of assets convicted of narcotics crime in the Supreme Court Decree Number 250K / Pid.Sus / 2018 was in accordance with the juridical basis namely the Criminal Procedure Code, Narcotics Law, and Government Regulation 40 of 2013, because the assets owned by the defendant amounted to Rp 142,131,500 (one hundred forty two one hundred thirty one five hundred billion), which is evidence number 11, 12, 13, and 14 (12 pieces of gold round rings, 14 rings of gold, 14 rounds of gold rings 8 pieces, and 1 piece of pendant) obtained before the delicti in casu tempus in 2009 until 2016 were returned to the defendant.